EDUKASI BAHAYA ANEMIA PADA REMAJA USIA SEKOLAH - Sri Legawati; Joni Siagian; Amelia Dini Anggraini Silalahi; Umi Kalsum; Sinta Juli Asmara; Syahidul Haq (LPPM AKPER GITA MATURA ABADI KISARAN, 2025)
Anemia is one of the health problems that often occurs in adolescents, both boys and girls, and has a significant impact on academic achievement, physical activity, and growth and development. This community service activity aims to increase the knowledge of students of SMA Negeri 1 Kisaran regarding the dangers of anemia and the importance of early prevention. The method used is health education through interactive counseling and distribution of educational leaflets in August 2023. A total of 80 students from grades X and XI participated. The pre-test results showed that only 35% of students had sufficient knowledge about anemia, while after intervention through education, this figure increased to 87.5%. This activity proves that school-based education is very effective in increasing student awareness of anemia. It is hoped that similar activities can be carried out periodically as part of the UKS and promotive-preventive programs in schools.